The perceived benefits and effectiveness of patient feedback systems in strengthening patient-provider relationships in Rural Tanzania - Kahabi Isangula; Eunice S. Pallangyo; Eunice Ndirangu-Mugo (BMC, 2023)
Abstract Introduction Patient feedback system (PFS) forms an important entry point for the medical personnel and healthcare administrators to identify healthcare service delivery gaps and develop responsive interventions. This may foster patient trust consequently increasing healthcare-seeking, engagement in decision, continuity, and satisfaction. However, research on the PFS in rural primary healthcare settings appears limited. Objective The paper examines the perceived role and effectiveness of PFS in improving therapeutic relationships building on the recent research on patient-provider relationships in rural Tanzania. Methods The paper examines the findings of qualitative descriptive research conducted in the Shinyanga Region which employed a human-centred design (HCD) approach to co-create an intervention package for improving nurse-client relationships between January and September 2022. The study used semi-structured interviews in Swahili to first explore drivers of poor provider-patient relationships with purposefully selected providers, patients, and administrators. The findings guided the co-designing of an intervention package in subsequent HCD steps. Interviews were concurrently translated and transcribed, then systematically coded to facilitate the development of themes using a deductive thematic analysis approach. Results PFS emerged as one of the key themes in the deductive analysis when examining factors shaping provider-client relationships. The PFS theme was characterized by three major subthemes, which included perceived benefits, availability and accessibility, and perceived effectiveness. The perceived benefits of PFS cited by most participants included: reducing patients' confusion around the complaints process, promoting patients' positivity towards providers and hospitals, and reducing tensions between patients and providers. Suggestion boxes (SBs) were the most frequently cited PFS, but there were widespread concerns and disagreements among participants about their accessibility and effectiveness. Despite the providers (nurses) and administrators describing SBs as widely available, they stated that they had not received feedback or complaints from patients for a very long time. In contrast, most patients stated that SBs were either unavailable or ineffective in many facilities, with concerns about non-user friendliness and lack of responsiveness as the main issues when discussing effectiveness. Conclusion Despite the many benefits of PFS in improving healthcare service quality, their availability, user-friendliness, and responsiveness still pose challenges. A call is made to providers, health administrators and researchers to prioritize the PFS as both a useful entry point to reducing tensions in therapeutic relationships and, a tool for improving patient service uptake, continuity of care and satisfaction.